Analysis Of Customer Satisfaction Level Of Quality Of Frontline Office Services Of BPJS Office Of Jambi Branch - Renny Listiawaty; Sugiarto Sugiarto (JURNAL WIDYA MEDIKA, 2020)
Customer satisfaction is important for service providers, customers will disseminate their satisfaction to prospective customers, thereby increasing the reputation of service providers. It is important for BPJS health, to continuously pay attention to the development of patient satisfaction. Of the 238 administrative complaints at the Jambi branch of the BPJS Health Office, there were 25 complaints of lack of information from frontline officers about the rights, obligations, and utilization of JKN cards so that customers felt less satisfied. This study aims to determine the level of satisfaction with the quality of frontline services at the Jambi Branch BPJS Health Office. The study was descriptive-analytic with a cross-sectional design. The sample of the study was 96 customers who visited the Jambi branch of the Health BPJS office and were taken by accidental sampling. The instrument is a questionnaire. Data were analyzed using Importance Performance Analysis (IPA). The study was conducted at the Jambi branch BPJS Office from January 26 to February 1, 2019. The level of customer satisfaction on tangible indicators was 84%, reliability was 83%, responsiveness was 88%, assurance was 92% and empathy was 88% and the average value - the suitability of all dimensions is 87%. Tangible and reliability indicators are still not satisfying customers. For this reason, it is hoped that the Jambi branch of BPJS Health will develop SOPs for frontline services and hold administrative service roleplay activities once a week.